On Elegant Labelling and Magic Labelling of Large-Scale Graphs - Jing Su; Hongyu Wang; Bing Yao (Discrete Dynamics in Nature and Society)
In this paper, we deduce the equivalence relationship among strongly c-elegant labelling, super-edge magic total labelling, edge antimagic total labelling, and super t,1-magical labelling. We study some properties of the graph with a strongly c-elegant labelling. On the basis of small-scale graphs with strongly c-elegant labelling, several types of large-scale graphs are constructed through graph operations, and we further prove the existence of their strongly c-elegant labelling. In addition, we also define a transformation of strongly c-elegant labelling, which provides a method for the transformation between several strongly c-elegant labellings of a graph.